Envisioning future travel: Moving from high to low carbon systems. (May 2019) - Fletcher, Jean; Longnecker, Nancy; Higham, James
Highlights: Expectations of travel becoming more environmentally sustainable were weakly correlated with levels of concern about climate change. Despite high levels of concern about climate change, only 48% of participants described travel in the year 2050 as having transitioned to low carbon mobility systems. Mapping responses to an Avoid/Shift/Improve framework revealed improved technology was the most discussed approach. Participants face trade-offs between their expectations regarding time, convenience, and monetary costs. Abstract: Comprehensive measures for reducing transport emissions were absent from the 2015 Paris Agreement yet without radical transformations in mobility systems and travel behaviour, transport emissions will continue to grow rapidly. This study investigated perceptions of travel in the year 2050 to see whether expectations of future travel align with lower carbon mobility systems. Data were collected through an international, online survey in 2016, targeting young adults with high levels of climate change concern. Thematic content analysis of responses (N = 401) revealed that 48% (n = 192) of participants described travel in 2050 as using low carbon mobility systems. This transition was predominantly attributed to improved technology (26%), rather than a shift in transportation mode (17%) or trip avoidance (12%). Expectations of future travel that could perpetuate high carbon mobility systems were mentioned by 53% (n = 212) of participants while only 23% (n = 94) mentioned factors that could reinforce low carbon mobility systems. These results show that even amongst people with high levels of concern about climate change, anticipated travel patterns have the potential to lock in high carbon transport and undermine progress. To achieve low carbon mobility transitions, strong international commitment must be supported by coordinated efforts of both governments and individuals.